Tyrosine Kinase Inhibitors in Lung Cancer - Thomas, Anish (2012)
‘Driver mutations’ are essential for carcinogenesis as well as tumor progression as they confer a selective growth advantage to cancer cells. Identification of driver mutations in growth related protein kinases, especially tyrosine kinases have led to clinical development of an array of tyrosine kinase inhibitors in various malignancies, including lung cancer. Inhibition of epidermal growth factor receptor and anaplastic lymphoma kinase tyrosine kinases have proven to be of meaningful clinical benefit, while inhibition of several other tyrosine kinases have been of limited clinical benefit, thus far. An improved understanding of tyrosine kinase biology has also led to faster drug development, identification of resistance mechanisms and ways to overcome resistance. In this review, we discuss the clinical data supporting the use and practical aspects of management of patients on epidermal growth factor receptor and anaplastic lymphoma kinase tyrosine kinase inhibitors.